Chlamydia trachomatis induces the transcriptional activity of host YAP in a Hippo-independent fashion - Caven, Liam T.; Brinkworth, Amanda J.; Carabeo, Rey A. (Frontiers in Cellular and Infection Microbiology, 2023)
The obligate intracellular pathogen Chlamydia trachomatis is the causative agent of the most common bacterial sexually transmitted disease worldwide. While the host response to infection by this pathogen has been well characterized, it remains unclear to what extent host gene expression during infection is the product of Chlamydia-directed modulation of host transcription factors. In this report, we show the transcriptome of Chlamydia-infected epithelial cells exhibits gene expression consistent with activity of YAP, a transcriptional coactivator implicated in cell proliferation, wound healing, and fibrosis. After confirming induction of YAP target genes during infection, we observed increased YAP nuclear translocation in Chlamydia-infected epithelial cells. We further show that increased YAP activation is a Chlamydia-directed process, requiring de novo protein synthesis during midcycle infection. Surprisingly, infection-mediated YAP activation bypasses YAP inhibition by the Hippo kinase cascade, with phosphorylation at S127 remaining unchanged. Instead, phosphorylation at Y357 was increased along with nuclear translocation, indicating that infection overrides phospho-inhibition at S127. Nuclear translocation of Y357F mutant YAP was not increased by infection, demonstrating that chlamydial YAP activation requires phosphorylation at this residue. Taken together, our results define a transcriptome-altering mechanism potentially linked to chlamydial fibrosis and other advanced disease sequelae.